CompTIA Project+ cert guide - Abernathy, Robin M. (Cert guide., 2018)
Learn, prepare, and practice for CompTIA Project+ PK0-004 exam success with this CompTIA-approved Cert Guide from Pearson IT Certification, a leader in IT certification learning and a CompTIA Authorized Platinum Partner. Master CompTIA Project+ PK0-004 exam topics Assess your knowledge with chapter-ending quizzes Review key concepts with exam preparation tasks Practice with realistic exam questions Gain even deeper understanding with more than 130 true-to-life project management examples CompTIA Project+ Cert Guide is a best-of-breed exam study guide. Project management certification expert Robin Abernathy shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. The book presents you with an organized test preparation routine through the use of proven series elements and techniques. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. Review questions help you assess your knowledge, and a final preparation chapter guides you through tools and resources to help you craft your final study plan. Through 130+ exceptionally realistic examples, Abernathy demonstrates how project management actually works throughout the phases, tasks, documents, and processes that are part of the project manager's job. These examples are designed to offer deep real-world insight that is invaluable for successfully answering scenario-based questions on the live Project+ exam. The companion website contains the powerful Pearson Test Prep practice test software, complete with hundreds of exam-realistic questions. The assessment engine offers you a wealth of customization options and reporting features, laying out a complete assessment of your knowledge to help you focus your study where it is needed most. Well regarded for its level of detail, assessment features, and challenging review questions and exercises, this CompTIA-approved study guide helps you master the concepts and techniques that will enable you to succeed on the exam the first time. The CompTIA-approved study guide helps you master all the topics on the Project+ exam, including . Project basics: properties, phases, roles, responsibilities, team structures, cost control, schedules, resource management, and Agile methodology . Project constraints, influences, and risks, including risk activities and strategies . Communication and change management, including communication methods, influences, triggers, target audiences, and change control . Project management tools, project documentation, and vendor documentation.